OPTIMASI SUDUT KEMIRINGAN PANEL SURYA PADA PROTOTIPE SISTEM PENJEJAK MATAHARI AKTIF - S. Tamimi; W. Indrasari; B. H. Iswanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The main problem on solar energy is instability power which generated by the solar panels, because it depends on the sunlight intensity which accepted by the solar panels. The intensity of sunlight received by the solar panels can be maximized by installing solar panels with a right angle so it will be obtained the maximum output power. This study has been carried out optimization angle of the solar panels that will be used on the active prototype solar tracking system. The optimization is taking the theta (Î¸) angle on the x negative axis by using the angle 0áµ’, 30áµ’, 45áµ’ and 60áµ’. The results showed that the average ouput power of the solar panels began to decline at 45áµ’. To find the best angle we tried to set the optimization at 10o, 20o, 25o, and 40o. Based on these studies an maximum  average power output is 73.17mW at the angle of 25o.Key words: solar panels, sunlight intensity, tilt angle, active solar tracker.